Laser-induced breakdown in air and behind droplets: a detailed Monte-Carlo simulation - Müsing, Andreas; Riedel, Uwe; Warnatz, Jürgen (Proceedings of the Combustion Institute, 2006)
Laser ignition has become an active research topic recently, due to the fact that it has the potential to replace the conventional electric spark plug in engines. In this work, a model for simulating the laser-induced breakdown in air and behind droplets is developed. The model is based on laser energy absorption by inverse bremsstrahlung and multiphoton ionization. A direct Monte-Carlo simulation is presented taking into account energy losses (via ionization, vibrational, and excitational losses) based on collision cross sections. For the first time breakdown behind the droplets of a fuel spray is modeled. The laser field intensity behind a droplet of spherical shape is calculated using Mie theory. The Monte-Carlo simulation is able to predict the minimum laser energy for breakdown. Simulations, as well as experimental results, are presented, varying the parameters gas pressure, laser pulse length, focal spot size of the focusing lens, and droplet size. The simulation results show good agreement with literature data of breakdown in clean air. Unclean environmental air shows a lower breakdown threshold in the experiments than in the simulation. Breakdown in the presence of fuel spray droplets shows much stronger dependency on the gas pressure and droplet size than breakdown in air without droplets.